Approval of Coercion in Psychiatry in Public Perception and the Role of Stigmatization - Steiger, Sahar; Moeller, Julian; Sowislo, Julia F.; Lieb, Roselind; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2022)
Background: Coercion is routinely used in psychiatry. Its benefits and drawbacks are controversially debated. In addition, the majority of persons with mental health problems are exposed to stigmatization and are assumed to be dangerous. Stigmatization is associated with negative consequences for individuals with mental illness such as disapproval, social rejection, exclusion, and discrimination. Being subjected to coercive measures can increase the stigmatization of the affected persons, and stigmatization might lead to higher approval for coercion. Aims of the Study: This study aims to examine the approval for coercive measures in psychiatry by the general public, and to explore its relation with person- and situation-specific factors as well as with stigmatization. Method: We conducted a representative survey of the general population (N = 2,207) in the canton of Basel-Stadt, Switzerland. Participants were asked to read a vignette depicting psychopathological symptoms of a fictitious character and indicate whether they would accept coercive measures for the person in the vignette. Desire for social distance and perceived dangerousness were assessed as measures of stigmatization. Findings: The person in the case vignette exhibiting dangerous behavior, showing symptoms of a psychotic disorder, being perceived as dangerous, and treatment being understood as helpful increased approval of coercion in general, while familiarity of the respondents with mental illness decreased approval. Conclusions: The public attitude regarding the approval of coercion in psychiatry is highly differentiated and largely follows the current legal framework and medical treatment guidelines. Higher approval occurred in situations of self-harm or harm to others and when coercive measures were thought to have a beneficial effect for the affected persons. A considerable part of the approval for coercion is predicted by stigmatization. With the increasing severity of coercive measures, the influence of person- and situation-specific factors and of familiarity with mental illness decreased and generalizing and stigmatizing attitudes became stronger predictors for the approval of more severe measures.